New species, records, and immature stages of Chimarra Stephens (Trichoptera: Philopotamidae) from Campos Amazônicos National Park, northern Brazil - Desidério, Gleison Robson; Barcelos-Silva, Patrik; Hamada, Neusa (Zootaxa, 2018)
Campos Amazônicos National Park is a federal conservation unit that contains part of the largest Cerrado refuge in the southern part of Brazilian Amazonia. Recently, during a survey of aquatic insects in the park, specimens of the caddisfly genus Chimarra were collected. The primary objective of this paper, as a result of this effort, is to describe and illustrate the male adult of a new species in Chimarra (Chimarrita), Chimarra singularis sp. nov., and the immature stages of Chimarra usitatissima Flint 1971. Additionally, the distributions of C.(Chimarrita) akantha Blahnik 1997 and C. (Curgia) jugescens Flint 1998 are extended to the southern part of Amazonas state, and C. (Chimarrita) heppneri Blahnik 1997 is recorded for the first time in northern Brazil.